Blood-brain barrier ion transport - O'Donnell, Martha (Henry Stewart Talks, 2008)
Ischemic stroke, Mechanisms of cerebral edema formation, Brain microvascular endothelial cell ion transporters and channels, Role of blood-brain barrier in water and electrolyte homeostasis in the brain, Potential blood-brain barrier therapeutic targets for ischemic stroke
Reviewed at 2016/12/19